2007
DOI: 10.1007/s00424-007-0383-3
|View full text |Cite
|
Sign up to set email alerts
|

A yeast-based phenotypic screen for aquaporin inhibitors

Abstract: Aquaporins mediate transport of water or small, uncharged solutes across cellular membranes according to the prevailing osmotic and chemical gradients. Because of their implication in human diseases and pathophysiological states, aquaporins are considered as potential drug targets. Yet, specific aquaporin inhibitors for in vivo studies are not available. Common functional aquaporin assays that monitor biophysical parameters related to volume changes, such as light scattering or fluorescence quenching, are time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…However, as soon as a functional methylamine transport facilitator is present in the plasma membrane (e.g. a L. bicolor aquaporin), methylamine can be released by yeast cells, which can be easily detected as yeast growth (Wu et al, 2008). The driving force for methylamine release is a pH gradient between cytosol (c. pH 7.2) and apoplastic space (pH 5.5 or 6.5 in the experiment).…”
Section: Glycerol Permeability Of L Bicolor Aquaporinsmentioning
confidence: 99%
“…However, as soon as a functional methylamine transport facilitator is present in the plasma membrane (e.g. a L. bicolor aquaporin), methylamine can be released by yeast cells, which can be easily detected as yeast growth (Wu et al, 2008). The driving force for methylamine release is a pH gradient between cytosol (c. pH 7.2) and apoplastic space (pH 5.5 or 6.5 in the experiment).…”
Section: Glycerol Permeability Of L Bicolor Aquaporinsmentioning
confidence: 99%
“…The purpose of the study was to demonstrate the presence of putative water channels, not shown to be present in these cells thus far, by using a set of commonly known aquaporin inhibitors. Mercury chloride (HgCl 2 ), a selective inhibitor of aquaporins (AQP) [17][18][19][20] was tested and its effects compared with those of AgNO 3 [18,21,22] and TEA [18,[23][24][25]. Calculations based on coarse physical parameters of P. noctiluca nematocytes and the OP duration yielded a low relative water permeability of ~10 -7 cm/sec, compared to most species with ~10 -3 cm/sec, an apparent evolutionary adaptation for Cnidarian survival.…”
Section: Introductionmentioning
confidence: 99%
“…A positive growth selection of yeast is possible by heterologous expression of an ammonia-facilitating AQP in a strain that lacks endogenous ammonium transporters (Holm et al, 2005). Phenotypic growth assays can be carried out in the presence or absence of putative AQP inhibitors either on solid agar media with photographic imaging of the cell density (Wu et al, 2008) or in liquid cultures by documenting the turbidity over time (Almasalmeh et al, 2014). The latter yields more quantitative data when integrating the areas under the curves from which IC 50 values can be…”
Section: Phenotypic Aqp Assaysmentioning
confidence: 99%